Implicit Racial identity of Russian Schoolchildren at the Commitment Stage - Алла А. Гудзовская; Марина С. Мышкина (Rossijskij psihologičeskij žurnal., 2021)
Introduction. The conditions of the transitivity in today’s social space, the interpenetration of different cultures, and the value of racial identity in racially heterogeneous societies such as Russian society, which historically represents two races (Caucasian and Mongoloid), explain the importance of studying racial identity. This study represents the first contribution to issues of implicit racial identity in Russian children. The authors introduce the concept of the commitment stage as a manifestation of interest in other groups, regardless of the consciousness or implicitness of individual identity. The theory of social identity and social categorization by G. Tajfel, J. Turner and the commitment approach in the models of the formation of racial identity by Yu. V. Stavropol'skii and J. Marcia provided a conceptual basis for this study. Methods. The research is based on an experiment with preferences. The respondents were offered photographs of faces of Caucasian, Mongoloid, and Equatorial races of different genders. They had to choose a partner for interaction in personal or social spheres. The number of choices and the number of categories used by the subjects during the experiment were calculated. Statistical tests and a one-way ANOVA were used. Results. This section contains data from the experimental study. The sample comprised of 290 individual participants (four age subgroups) aged 7–11 years. There were no significant differences among age subgroups (grades 1, 2, 3, and 4) in terms of racial preferences. Gender effects racial preferences. The leading factor influencing preferences when choosing a partner for interaction by photographic images is his/her gender (same- vs. opposite-gender individuals). Discussion. The authors interpret the results of choosing a partner for interaction as an indication of implicit identity and note that the criterion of ‘racial identity’ has an insignificant impact on the process of social categorization by Russian primary schoolchildren. Russian schoolchildren are interested in interacting with children of all races, that is, their implicit racial identity is at the commitment stage.